2013
DOI: 10.1097/ccm.0b013e318275cee7
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Burn Progression Decreased by Erythropoietin*

Abstract: Erythropoietin represents an easy-to-use therapeutic approach to prevent secondary burn progression, i.e., to control damage after burn injury. It preserves microcirculatory perfusion within the endangered areas in a dose-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In ischemic musculocutaneous skin flaps, Epo administration up-regulates eNOS and the protective effect is abrogated by administration of eNOS inhibitors ( 56 ). Administration of Epo has also been shown to reduce the depth and area of secondary burn progression ( 57 ). These extra-hematopoietic eNOS dependent protective actions may result, at least in part, from vasodilation with increased blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In ischemic musculocutaneous skin flaps, Epo administration up-regulates eNOS and the protective effect is abrogated by administration of eNOS inhibitors ( 56 ). Administration of Epo has also been shown to reduce the depth and area of secondary burn progression ( 57 ). These extra-hematopoietic eNOS dependent protective actions may result, at least in part, from vasodilation with increased blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…In our review, several studies over the last five years examined the role of erythropoietin (EPO), a hormone with known anti-inflammatory, angiogenic, and vasodilatory properties [7476], in the prevention and treatment of burn wound progression [75]. Tobalem et al demonstrate that treatment with EPO limits interspace necrosis and burn depth extension in a dose-dependent manner in a comb burn model [76].…”
Section: Discussionmentioning
confidence: 99%
“…Turkaslan et al investigated the effects of HBOT in the zone of stasis and reported increased cells in the synthesis stage by 24 hours post-burn, increased radioactive uptake by 5 days post-burn, and decreased necrosis overall in the treatment group [75]. Similar to the study by Tobalem et al [93, 94], new vessel formation was not significantly different between the treatment and control group in the early critical stages of burn wound progression, suggesting a less important role for neoangiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…73,76 In 2012, Tobalem et al 77 reported that the early treatment of burns with systemic EPO prevented secondary burn progression by improving vascular perfusion within the endangered area in a dose-dependent manner. In a follow-up study, the same investigators 78 reported that increased iNOS expression and suppression of the inflammatory response were the underlying mechanisms of EPO's preventative actions on secondary burn progression. Interestingly, Bohr et al 79 reported that EPO derivatives that can trigger EPO-mediated signaling but do not bind to the EPOR homodimer, such as the helix β-surface peptide (ARA290), can reduce burn depth and area and protect burn wounds from deteriorating in mice with a skin burn.…”
Section: Epo and Wound Healing: Animal Study Findingsmentioning
confidence: 96%
“…reported that the early treatment of burns with systemic EPO prevented secondary burn progression by improving vascular perfusion within the endangered area in a dose‐dependent manner. In a follow‐up study, the same investigators reported that increased iNOS expression and suppression of the inflammatory response were the underlying mechanisms of EPO's preventative actions on secondary burn progression. Interestingly, Bohr et al .…”
Section: Epo and Wound Healing: Animal Study Findingsmentioning
confidence: 98%